Impactor relics of CI-like chondrites in Chang’e-6 lunar samples - Jintuan Wang; Zhiming Chen; Zexian Cui; Qing Yang; Le Zhang; Pengli He; Jingyou Chen; Chengyuan Wang; Yan-Qiang Zhang; Jiangze Wang; Yonghua Cao; James W. Head; et al. (Proceedings of the National Academy of Sciences, 2025)
The impact history of the Moon provides the opportunity to better understand mass transfer in the Solar System. While Earth’s meteorite collection serves as a key reference for material flux in the Earth–Moon system, it suffers from profound biases arising from Earth’s orbital dynamics and atmospheric filtering. Systematic identification and classification of meteorites on the airless Moon thus provide additional critical constraints for reconstructing the primordial accretion history and impactor population of the inner Solar System. However, identifying impactors on the Moon remains challenging due to their vaporization upon colliding at high velocities with the lunar surface. In situ remote sensing has previously detected chondritic impactor materials in the South-Pole-Aitken (SPA) basin of the far side of the Moon. The first opportunity to measure materials from the SPA basin has come via the Chang’e-6 (CE-6) mission, which returned samples from the Apollo basin inside the SPA basin. In this study, we screened seven olivine-porphyritic clasts as potential impactor relics in regolith returned by the CE-6 mission. These clasts were identified, via textural characterization, olivine Fe–Mn–Zn systematics, and in-situ triple oxygen isotopes, as impact relics solidified from melted chondritic parent bodies. Intriguingly, the parent body of all the identified impactor relics in this study resemble CI-like chondrites, a volatile-rich meteorite group that is relatively rare in Earth’s meteorite collection. The detection and classification of these impactor relics impose significant constraints on the proportions of meteoritic materials in the Earth–Moon system and their potential contributions to water inventories on the lunar surface.